2014
DOI: 10.5172/conu.2014.4788
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and Physicians’ Perceptions of Older People and Attitudes towards Older People: Ageism in a Hospital in Turkey

Abstract: Nurses and physicians provide health care for a growing number of older people as a result of the rapid increase in the life expectancies of older people. Health professionals' negative attitudes towards older people affect the quality of health care offered to these individuals. The sample for this study included 110 nurses and 57 physicians working in the medical and surgical clinics of a university hospital. A questionnaire form and the Ageism Attitude Scale (AAS) were used to collect the data. A 5-point Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 17 publications
3
23
1
13
Order By: Relevance
“…2015) used the Kogan Attitudes towards Old People (KATOP) scale to assess attitudes towards older adults; one using it indirectly to measure attitudes towards older people with respect to the difficulties they experienced in older patient care. Four studies used researcher developed Likert‐style surveys including the Ageism Attitude Scale measuring positive/negative discrimination (Polat, Karada, Ülger, & Demir, ), a scale for measuring nurses' perceptions of care of older people (Eloranta et al., ) and a scale measuring attitudes towards the care of elderly; nurse‐patient ratio and care of the elderly; factors influencing care of the elderly and knowledge of the ageing process (Oyetunde et al. ).…”
Section: Presentation Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2015) used the Kogan Attitudes towards Old People (KATOP) scale to assess attitudes towards older adults; one using it indirectly to measure attitudes towards older people with respect to the difficulties they experienced in older patient care. Four studies used researcher developed Likert‐style surveys including the Ageism Attitude Scale measuring positive/negative discrimination (Polat, Karada, Ülger, & Demir, ), a scale for measuring nurses' perceptions of care of older people (Eloranta et al., ) and a scale measuring attitudes towards the care of elderly; nurse‐patient ratio and care of the elderly; factors influencing care of the elderly and knowledge of the ageing process (Oyetunde et al. ).…”
Section: Presentation Of Resultsmentioning
confidence: 99%
“…Nurses held both positive and negative attitudes towards caring for older adults. Six studies reported nurses' overall positive attitudes (Adibelli & Kilic, ; Eloranta et al., ; Gillis, MacDonald, & MacIsaac, ; Liu, Norman, & While, ; Oyetunde, Ojo, & Ojewale, ; Polat et al., ), and two studies reported nurses' overall negative attitudes towards older adult care (De Almeida Tavares et al., ; Higgins et al., ).…”
Section: Presentation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polat et al indicated that ageist attitudes among Turkish healthcare providers were not related to demographic characteristics such as age, gender, and education level (12). Usta et al found a correlation between gender and positive ageism among Turkish nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating ageist attitudes among nursing students, nurses, and physicians in the Turkish context demonstrated that Turkish healthcare providers' attitudes toward older individuals were generally positive (11)(12)(13). However, to the best of our knowledge, no studies have evaluated ageist attitudes of Turkish nursing staff and its relation with occupational burnout and job satisfaction.…”
Section: Ageism In Nursing Staffmentioning
confidence: 98%